Engineering Orthogonal Methyltransferases to Create Alternative Bioalkylation Pathways. (22nd June 2020) - Herbert, Abigail J.; Shepherd, Sarah A.; Cronin, Victoria A.; Bennett, Matthew R.; Sung, Rehana; Micklefield, Jason
Abstract: S ‐adenosyl‐l ‐methionine (SAM)‐dependent methyltransferases (MTs) catalyse the methylation of a vast array of small metabolites and biomacromolecules. Recently, rare carboxymethylation pathways have been discovered, including carboxymethyltransferase enzymes that utilise a carboxy‐SAM (cxSAM) cofactor generated from SAM by a cxSAM synthase (CmoA). We show how MT enzymes can utilise cxSAM to catalyse carboxymethylation of tetrahydroisoquinoline (THIQ) and catechol substrates. Site‐directed mutagenesis was used to create orthogonal MTs possessing improved catalytic activity and selectivity for cxSAM, with subsequent coupling to CmoA resulting in more efficient and selective carboxymethylation. An enzymatic approach was also developed to generate a previously undescribed co‐factor, carboxy‐ S ‐adenosyl‐l ‐ethionine (cxSAE), thereby enabling the stereoselective transfer of a chiral 1‐carboxyethyl group to the substrate. Abstract : Methyltransferase enzymes (MTs) selectively deliver methyl substituents to an array of molecules, thereby controlling gene expression or modulating the bioactivity of therapeutically important natural products. A MT was engineered for selective carboxy(m)ethylation to give an orthogonal MT that was combined with the SAM‐derivatising enzyme CmoA to create new carboxymethylation pathways.